Some economics of banking reform - Vickers, J (University of Oxford, 2012)
Where do we stand, five years on from the start of the crisis, on progress towards banking reform? Major advances have been made, but a lot of unfinished business remains, notably on structural reform of banks. Following a stock-take of current reform initiatives, the paper reviews some economics of public policy towards banks, starting with the rationale for deposit guarantees and lender-of-last-resort support but concentrating on why governments feel compelled to provide solvency support in crisis. It then covers the economics of capital requirements